Stereoselective oxidation of regioisomeric octadecenoic acids by fatty acid dioxygenases - Oliw, Ernst H.; Wennman, Anneli; Hoffmann, Inga; Garscha, Ulrike; Hamberg, Mats; Jernerén, Fredrik (Journal of lipid research, 2011)
Seven Z-octadecenoic acids having the double bond located in positions 6Z to 13Z were photooxidized. The resulting hydroperoxy-E-octadecenoic acids [HpOME(E)] were resolved by chiral phase-HPLC-MS, and the absolute configurations of the enantiomers were determined by gas chromatographic analysis of diastereoisomeric derivatives. The MS/MS/MS spectra showed characteristic fragments, which were influenced by the distance between the hydroperoxide and carboxyl groups. These fatty acids were then investigated as substrates of cyclooxygenase-1 (COX-1), manganese lipoxygenase (MnLOX), and the (8R)-dioxygenase (8R-DOX) activities of two linoleate diol synthases (LDS) and 10R-DOX. COX-1 and MnLOX abstracted hydrogen at C-11 of (12Z)-18:1 and C-12 of (13Z)-18:1. (11Z)-18:1 was subject to hydrogen abstraction at C-10 by MnLOX and at both allylic positions by COX-1. Both allylic hydrogens of (8Z)-18:1 were also abstracted by 8R-DOX activities of LDS and 10R-DOX, but only the allylic hydrogens close to the carboxyl groups of (11Z)-18:1 and (12Z)-18:1. 8R-DOX also oxidized monoenoic C14-C20 fatty acids with double bonds at the (9Z) position, suggesting that the length of the omega end has little influence on positioning for oxygenation. We conclude that COX-1 and MnLOX can readily abstract allylic hydrogens of octadecenoic fatty acids from C-10 to C-12 and 8R-DOX from C-7 and C-12.